Tеоретико-практичні аспекти державної антикризової політики в туристичному бізнесі - Маркіна, І.А. (Культура народов Причерноморья, 2013)
В статті надається визначення та характеристика основних засад державної антикризової політики в туристичному бізнесі, визначаються існуючі нагальні проблеми. Автором узагальнено та обґрунтовано поняття антикризової політики в туристичному бізнесі та запропоновано основні заходи щодо її удосконалення. Ключові слова: антикризова політика, державна антикризова політика, державне регулювання, туристичний бізнес, туристична інфраструктура, туристичний потенціал. В статье дается определение и характеристика основных принципов государственной антикризисной политики в туристическом бизнесе, определяются существующие насущные проблемы. Автором обобщено и обосновано понятие антикризисной политики в туристическом бизнесе и предложены основные мероприятия по ее усовершенствованию. Ключевые слова: антикризисная политика, государственная антикризисная политика, государственное регулирование, туристический бизнес, туристическая инфраструктура, туристический потенциал. In this article we present a definition and description of the main principles of the state anti-crisis policies in the tourism business determined by current pressing issues. The author summarized and substantiated the concept of anti-crisis policies in the tourism business and the key actions proposed for its improvement. In the public administration in general to understand the system of executive, whose main activity is the implementation of measures for the legislative and regulatory framework. One of the essential features of public administration is subordinate, secondary nature compared to legislative activity Crisis management includes a set of methods used in different functional subsystems management. In particular, social technologies, methods of economic analysis, forecasting, development of complex investment projects and crisis programs, restructuring and reorganization plans which are used in combination for early warning and crisis management. Varied program of tourism development that are designed for different time periods do not include the possibility of occurrence of uncertainty and risk, and, moreover, do not provide recommendations for management actions for their conditions. The results suggest that in order to optimize the impact of the current regulatory framework of state regulation on the development of tourism is necessary to develop anti-crisis policy, which is aimed at overcoming the crisis of the subject to the influence of negative factors functioning. Keywords: anti-crisis policy, government anti-crisis policy, government regulation, tourism, tourism infrastructure, tourism potential.